Possible biotic interactions that are affecting the presence of Aedes albopictus (Diptera: Culicidae) in Misiones, Argentina - Lizuain, Arturo A. (2022)
In Argentina, despite local Aedes albopictus presents a certain degree of egg dormancy that would allow to be present at temperate latitudes its distribution is limited to two provinces with a subtropical climate: Misiones and Corrientes. Therefore, it is possible that other factors are limiting the expansion of this vector. To evaluate possible interactions that are affecting population and spread of this specie, we sampled artificial breeding site in Eldorado (urban environment) and Colonia Aurora (rural environment), Misiones province, in October 2015, April and November 2016 and April 2017.